2021
DOI: 10.1007/s11764-021-01117-4
|View full text |Cite|
|
Sign up to set email alerts
|

The current status of survivorship care provision at the state level: a Wisconsin-based assessment

Abstract: Purpose As the number of cancer survivors grows, the responsibility for addressing their unique physical and emotional needs also increases. Survivorship care services vary by geography, health system, and insurance coverage. We aimed to understand the state of survivorship care services in Wisconsin’s cancer facilities. Methods The selection of cancer treatment facilities sought to provide a geographically representative sample. An adapted Patient-Centered Survivorship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…6 In fact, few studies provide details of reimbursement for survivorship visits, although a growing literature describes barriers to adequate reimbursement for managing physical, social, and emotional side effects or care coordination. 6,54-57 A recent publication included a quote from a cancer center key informant that, “we're not able to get insurers to pay for survivorship visits”; this comment was later clarified as focusing on the lack of reimbursement for preparing treatment summaries and care plans. 55 Similarly, a study describing survivorship clinics in Wisconsin suggested that mental health services, exercise/lifestyle services, sexual health, and fertility counseling were underrepresented at survivorship clinics because of lack of adequate insurance coverage of these services.…”
Section: Presumption: Survivorship Clinics Lose Moneymentioning
confidence: 99%
See 1 more Smart Citation
“…6 In fact, few studies provide details of reimbursement for survivorship visits, although a growing literature describes barriers to adequate reimbursement for managing physical, social, and emotional side effects or care coordination. 6,54-57 A recent publication included a quote from a cancer center key informant that, “we're not able to get insurers to pay for survivorship visits”; this comment was later clarified as focusing on the lack of reimbursement for preparing treatment summaries and care plans. 55 Similarly, a study describing survivorship clinics in Wisconsin suggested that mental health services, exercise/lifestyle services, sexual health, and fertility counseling were underrepresented at survivorship clinics because of lack of adequate insurance coverage of these services.…”
Section: Presumption: Survivorship Clinics Lose Moneymentioning
confidence: 99%
“…55 Similarly, a study describing survivorship clinics in Wisconsin suggested that mental health services, exercise/lifestyle services, sexual health, and fertility counseling were underrepresented at survivorship clinics because of lack of adequate insurance coverage of these services. 57 Yet, profit or reimbursement was not directly evaluated.…”
Section: Presumption: Survivorship Clinics Lose Moneymentioning
confidence: 99%